The Impact and Application of Nanotechnology on Human Resource Management - Derakhshanian, Hooman (Prabandhan: Indian Journal of Management, 2013)
Nanotechnology is a modern science, and its applications are gradually appearing in different sciences. Though these applications are obvious in basic sciences, medicine, and engineering sciences, etc., it is difficult to explain the right usage of nanotechnology in abstract sciences as it depends on the foremost definition of discussing matter. One of the most prominent fields in which the definition of nanotechnology is most important is Management. This study tries to provide a point of view on definition and type of nanotechnology application in management. The purpose of this study is expanding, making more flexible, discovering various parts, levels, structures, and secrets of organizations and management knowledge by benchmarking from Nano science and surely, its findings show so many similarities between these which are visible and require thinking. Obviously, Nanotechnology would be effective in the development of different sciences and shall pose a challenge for human resource management in various parts such as adjustability of organizations, and as a result, accelerating the organizations' Nanotechnology development. Organizations must adopt these developments by using appropriate structural policies. In the present paper, I examine two points of view: The effect of Nanotechnology on human resource management; and also the application of Nanotechnology in the HR department of organizations.